Neutrosophic Soft Multi-Attribute Group Decision Making Based On Grey Relational Analysis Method - Partha Pratim Dey; Surapati Pramanik; Bibhas C Giri (Journal of New Results in Science)
The objective of the paper is to present neutrosophic soft multi attribute group decision making based on grey relational analysis involving multiple decision makers. The concept of neutrosophic soft sets is derived from the hybridization of the concepts of neutrosophic set and soft set. In the decision making process, the decision makers offer the rating of alternatives with respect to the parameters in terms of single valued neutrosophic set. We utilize AND operator of neutrosophic soft sets in order to aggregate the individual decision maker’s opinion into a common opinion based on choice parameters of the evaluator. Then, information entropy method is employed in order to attain the weights of the choice parameters. We determine the order of the alternatives and identify the most suitable alternative based on grey relational analysis. Finally, in order to show the effectiveness of the proposed approach, a numerical example is solved